A survey of Chinese consumers' knowledge, beliefs and behavioural intentions regarding salt intake and salt reduction. Issue 8 (13th June 2020) - Chen, Si; Shan, Liran Christine; Tao, Wanting; Lu, Ting; Regan, Áine; Han, Hongwei; Guo, Lixia; Deng, Taotao; Wall, Patrick
Abstract: Objective: Globally, China is among the 'saltiest' nations. In order to support current nationwide salt reduction initiatives, we investigated Chinese consumers' knowledge, beliefs and behaviours related to salt intake and salt reduction. Design: A cross-sectional face-to-face survey was carried out, focusing on salt knowledge, beliefs and behaviours related to salt intake and salt reduction, perceptions of salt reduction responsibility and support for different national strategies. Setting: The survey was carried out in China mainland. Participants: Consumers ( n 2444) from six of seven major geographical regions in China participated in the survey. After data cleaning, a sample of 2430 was included in the final analysis. Results: A majority of Chinese consumers believed that salt added during home cooking was the biggest contributor to their salt intake. Knowledge gaps existed in the awareness of salt hidden in certain foods and flavouring products. Chinese consumers in general were interested in lowering their salt intake. They were aware of salt reduction tools, but the adoption level was low. Consumers expressed strong support for promotion of salt-restriction spoons and public education, but not fiscal policies (e.g. salt-related tax or subsidies). In terms of individual differences, education status demonstrated a substantial impact on salt reduction knowledge and behaviour. Conclusions: There is still big room to 'shake' Chinese consumers' salt habit. The present study provides important evidence and consumer insights to support China's efforts to meet its salt reduction targets.